Interactive buckling in sandwich beam-columns - Wadee, M. Ahmer; Yiatros, Stylianos (My University, 2011)
Recent work on localized buckling with different core bending theories in sandwich struts is adapted for a sandwich beam-column that combines the effects of bending and compression. The two distinct bifurcations present in the pure compression case are replaced by a single pitchfork bifurcation point that combines local and global buckling behaviour. Several models with a various number of degrees of freedom (DOFs) are developed to account for the explicit effect of end moments. All models are formulated using total potential energy and variational principles, which are used to derive the governing equations that are solved using the numerical continuation package AUTO97. Results are validated with a finite element model formulated in the commercial package ABAQUS. Comparisons with the interactive buckling profiles and the mechanical response in the nonlinear range are very favourable and the models with more DOFs are determined to be superior.
Keywords: Nonlinear mechanics; Buckling; Composites